Preliminary in vivo evaluation of anti-inflammatory activities of aqueous and ethanolic whole plant extracts of Phyllanthus fraternus on Carrageenan-induced Paw Oedema in Sprague-Dawley Rats - Oseni L.A., Amiteye D., Antwi S., Tandoh M., Aryitey G.M. (Journal of Applied Pharmaceutical Science, 2013)
Medicinal plants represent potential sources for the discovery of new anti-inflammatory agents. Aqueous and ethanolic whole plant extracts of Phyllanthus fraternus were evaluated in vivo for their anti-inflammatory activities on carrageenan-induced paw oedema in Sprague-Dawley rats. The extracts were also screened for phytochemicals. Some of the phytochemicals found in the extracts have previously been implicated as anti-inflammatory agents. The LD50 of both extracts was investigated and found to be greater than 5000mg/kg. The extracts at doses 100mg/kg and 200mg/kg showed modest anti-inflammatory activity in a dose dependent manner. The aqueous extract demonstrated better inhibition of paw oedema compared with the ethanolic extract at 200mg/kg after 4hrs. The activity of the standard drug, indomethacin at 25.0 mg/kg was significantly higher (p
Keywords: In vivo anti-inflammatory, Phyllanthus frat